Unpacking the Code: Exploring Teachers’ Professional Development in Reading - Beach, Pamela; McConnel, Jen; Mendes, Barbara (Journal of the Canadian Association for Curriculum Studies, 2020)
Teaching reading requires considerable knowledge and skill acquired over several years, and while communities and families contribute to students’ reading success, teachers are the most influential forces for delivering high-quality reading programs. Professional development opportunities in reading enable teachers to augment their current curriculum content and pedagogical knowledge and can have a powerful effect on their practice and, ultimately, on student learning. We conducted a qualitative study exploring teachers’ perceptions of reading development and instruction with nine elementary educators enrolled in a targeted professional development course. Two semi-structured interviews were conducted: once prior to the start of the professional development course and once following the professional development course. An inductive approach to analysis resulted in four main themes: seeking out new knowledge, evolving definitions of reading, transformative learning moments, and increases in self-efficacy for teaching reading. This study illustrates the transformative power a targeted professional development course can have on teachers’ perceptions of reading. Professional development in reading that is relevant and properly resourced can significantly impact teachers’ perceptions of their practice, their self-efficacy for teaching reading and, ultimately, have a positive effect on their students’ growth in reading development. Additionally, understanding teachers’ perceptions of their professional development in reading can contribute to the development and refinement of professional learning experiences.